معالم التربية الجهادية في سورة التوبة وكيفية الاستفادة منها : دراسة تحليلية - Maher Ghazali (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The purpose of this research is to illustrate the characteristics of education on Jihad in Surat al-Tawbah through an analytical study of its ayat. Some of the educational parameters that have a direct connection to the subject of jihad for the sake of Allah have been identified in various issues. Jihad education would help in safeguarding the Muslim society, as well as to tackle the dangers of deviant teachings that create spiritual social and political problems. This study adopted two scientific methods: inductive method, by which relevant ayat from the Qur'an al-Karim in general were collected, and from Surah at-Tawbah in particular, and their interpretations from the traditional as well as the modern commentaries of the Qur'an. The second method is analytical which was adopted in analyzing the verses of Surah Al-Tawbah, comparing the opinions of the Mufassirin (Qur'anic commentators), in juridical rulings, issues of Jihad and its meanings in an attempt to develop the characteristics of education on Jihad in Islam. The study reached certain conclusions as follows: that jihad education is a comprehensive integrated educational process, that does not only concern one aspect of the life of Mujahid, but it transforms his total being. In addition, the Surah Tawbah teaches us through these educational dimensions the importance of firm belief system [aqidah] in the life of not only Mujahid, but Muslims in general. This, indeed, is a basic foundation on which all other actions and devotions depend. Due to its paramount importance, the Prophet (pbuh) constantly taught his companions and trained them on this foundation of Iman. These teachings of the Surah were the divine lights for the believers involved in Jihad fi sabilillah [struggle for the cause of Allah], and the whole Muslim Ummah in general. Hence it is the duty of all Muslims to search, identify, reflect upon and implement them in their lives as Muslim believers.